2003
DOI: 10.1200/jco.2003.04.176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endothelin-A Receptor Blockade With Atrasentan on Tumor Progression in Men With Hormone-Refractory Prostate Cancer: A Randomized, Phase II, Placebo-Controlled Trial

Abstract: Atrasentan is an oral, targeted therapy with favorable tolerability and the potential to delay progression of HRPCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
179
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 340 publications
(190 citation statements)
references
References 30 publications
6
179
0
4
Order By: Relevance
“…13 Among evaluable patients, there was a significant difference in time to progression between the 10-mg atrasentan group and the placebo group (196 days vs. 129 days, P ¼ .02). There was also a significant improvement in time to PSA progression (155 days vs. 71 days, P ¼ .002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Among evaluable patients, there was a significant difference in time to progression between the 10-mg atrasentan group and the placebo group (196 days vs. 129 days, P ¼ .02). There was also a significant improvement in time to PSA progression (155 days vs. 71 days, P ¼ .002).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Phase II studies in prostate cancer suggested that atrasentan had modest clinical activity, with statistically significant improvement in time to disease progression, time to prostatespecific antigen (PSA) progression, and changes in bone turnover markers compared with placebo. 9,13 Men with metastatic HRPC treated with placebo exhibited a continued increase in bone alkaline phosphatase (BAP), a marker of osteoblast activity, and N-telopeptide (NTX), a marker of osteoclast activity. Treatment with atrasentan blocked the increase in BAP and, to a lesser extent, attenuated the increase in NTX.…”
mentioning
confidence: 99%
“…a factor in tumor growth. Randomized placebo-controlled Phase II studies demonstrated a consistent ability of atrasentan to attenuate the increase in markers of prostate cancer progression such as prostate-specific antigen, alkaline phosphatase, Ntelopeptides, C-telopeptides, deoxypyridinoline, and lactate dehydrogenase (22)(23)(24). Phase III trials comparing atrasentan to placebo are nearing completion.…”
Section: Discussionmentioning
confidence: 99%
“…However, in common with other targeted therapies, and unlike cytotoxic therapies such as docetaxel, phase II data for atrasentan are consistent with cytostasis, leading to delays in progression rather than a reduction in tumour burden. 63 For the time being, the role of these agents remains in doubt as the results of phase III trials mature. Nonetheless, the eventual introduction of the new targeted therapies that are now in clinical development will be an important step in the management of HRPC.…”
Section: Future Directionsmentioning
confidence: 99%